A Study on Drug Utilisation Pattern of Acei in an Indian Multispeciality Hospital - Duraisingh, Britto L; A, Chalasani; S, Ponsubharam; R, Vijayaraguvaran; V, Sankar (Asian Journal of Pharmaceutical Research and Development, 2013)
Irrational drug use mainly affects the patient safety and efficacy. Coordinated effects between healthcare workers are essential to make rational drug use a reality.To promote appropriate drug use in multispeciality hospital for ramipril and enalapril [Angiotensin converting enzyme inhibitors (ACEI’s)]. A randomised observational and interventional study was carried out for six month period for ramipril and enalapril.We monitored drug use, drug efficacy and cost effectiveness of two drugs. Study results showed that inappropriateness was high in monitoring adverse events and drug-drug interactions in contrast dose and medication adherence was found to be appropriate; ACEI’s were compared for their efficacy using blood pressure and found ramipril had more activity. Incremental cost effective ratio analysis was done for two drugs; ramipril was more cost effective with lowest cost ratio when compared to enalapril. The obtained results were disseminated along with criteria to physician; Feedback was obtained from the physician in the form of standard questionnaire.This study proved that drug utilisation studies are effective in improving prescribing practice and reducing treatment errors that directly helps to promote appropriate drug use.